CRITICAL ANALYSIS OF MENTAL HEALTH SUPPORT SERVICES AND ASSESSING ACCESSIBILITY, EFFECTIVENESS, AND INTEGRATION IN HEALTHCARE DELIVERY SYSTEMS - Mosfer Saeed Mezher Alkathami, ‏Afaf Saleeh Alnahdi, ‏Nawal Adbualaziz Alzahrani, Mohammed Marii Mohammed Alqarni, Tariq Rabeh Alharby, Ali Gourab Marrzoq Al-Sogour, ‏Amani Faisal Nahhas, Mariam Mohammed Alsiary, (Chelonian Research Foundation, 2022)
Mental health support services are an essential mechanism for reducing the global mental burden. Though some hurdles facing the effort are inadequate, among others are a lack of accessibility and effectiveness and strenuous integration into healthcare delivery. This is a critical analysis of the services provided in the mental health sector, including the traditional therapeutic approach, innovative digital mental health platforms, and community programs. This paper conducts a deep search for the existing literature and case studies to assess the level of accessibility of mental health services and evaluate the efficiency of those in helping patients achieve the set goals and strategies for a smooth integration of mental health services into the existing mainstream medical service systems. The paper leads the readers through critical factors such as stigma alleviation, cultural competency, and stakeholder collaboration by solving mental health service complications. The result indicates that holistic and personalized mental health support is welcomed. As for care in healthcare settings, continuous efforts need to be engaged in widening horizons in accessibility, effectiveness, and integration of mental health care. Keywords: support services, mental health, quality of delivery, integration of services, delivery systems, stigmatization